2016
DOI: 10.3892/ol.2016.4360
|View full text |Cite
|
Sign up to set email alerts
|

A double suicide gene system driven by vascular endothelial growth factor promoter selectively kills human hepatocellular carcinoma cells

Abstract: Abstract. The aim of the present study was to investigate the selective killing effect on hepatocellular carcinoma (HCC) cells of an adenovirus (Ad)-mediated cytosine deaminase (CD) in combination with thymidine kinase (TK) suicide gene system, driven by the vascular endothelial growth factor promoter (VEGFp), in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…It is tempting to assume that a promoter of a well-known tissue-specific gene can drive tissue-specific expression when cloned upstream of a transgene [54]. For example, gene therapy strategies targeting vascular endothelial cells frequently utilize a promoter of vascular endothelial growth factor [89]. The problem is that the activity of the proximal promoter might be modified by the genomic context, nearby enhancers, epigenetic modifications, miRNA-binding sites, the 3 0 untranslated region (UTR), etc.…”
Section: Box 4 a Practical Application: A Systematic Approach To Conmentioning
confidence: 99%
“…It is tempting to assume that a promoter of a well-known tissue-specific gene can drive tissue-specific expression when cloned upstream of a transgene [54]. For example, gene therapy strategies targeting vascular endothelial cells frequently utilize a promoter of vascular endothelial growth factor [89]. The problem is that the activity of the proximal promoter might be modified by the genomic context, nearby enhancers, epigenetic modifications, miRNA-binding sites, the 3 0 untranslated region (UTR), etc.…”
Section: Box 4 a Practical Application: A Systematic Approach To Conmentioning
confidence: 99%
“…The main obstacle is that these cancer stem cells are often in a state of dormancy which impairs the treatment effects of chemotherapeutic drugs (9). Some recent studies have shown that the herpes simplex virus thymidine kinase (HSVtk) gene and the complementary treatment with ganciclovir (GCV) exert marked antitumor effects against HCC by promoting apoptosis and inhibiting angiogenesis (10,11). However, it is still difficult to prevent the recurrence of liver tumors (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that normal gap junction intercellular communication (GJIC) between tumor cells is crucial for HSVtk/GCV to exert its therapeutic effects (10). However, there are few studies on the structure and function of GJIC between liver cancer stem cells, although some studies have reported that their GJIC is obviously defective in liver tumors (13).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, gene therapy has proven to be an emerging and efficient means of cancer treatment [14, 15] and has entered clinical trials. A phase III clinical trial of suicide gene therapy using retrovirus-mediated transduction in glioblastoma failed to show improvements in survival outcomes by systemic viral administration owing to a failure to achieve a therapeutic dose of transgene expression at the site of disease [8, 16]. Free flaps may provide an alternative approach to systemic viral administration.…”
Section: Discussionmentioning
confidence: 99%